SAN’ATNING SHAXSGA TA’SIRI - ramazon, zubaydullayev1 (Maktabgacha taʼlim jurnali, 2022)
The article focuses on the impact of art on the individual in the preparation of future teachers for professional activities on the basis of art pedagogy, and the issues of building skills for its comprehensive use in the educational process.